72 Offset of ticagrelor prior to coronary artery bypass graft surgery (cabg) surgery. (5th June 2017) - Weng Ow, Kok; Thomas, Mark; Parker, William; Judge, Heather; Storey, Robert
Abstract : Introduction: Ticagrelor is a more potent platelet inhibitor than clopidogrel but also has a more rapid offset of inhibitory effect. The optimal timing of discontinuation of ticagrelor prior to coronary artery bypass graft (CABG) surgery is unknown. In the ONSET/OFFSET study of patients with stable coronary artery disease, ticagrelor's effects dissipated within 48–120 hours of discontinuation. However, there is evidence that the pharmacodynamics of antiplatelet therapy are significantly altered during an acute coronary syndrome (ACS) and the ONSET/OFFSET study results should not be extrapolated to ACS patients. Although the PLATO study suggested that it was safe to discontinue ticagrelor 48 hours prior to CABG, regulatory authorities recommended that ticagrelor should be discontinued 5 days prior to CABG. The PLATO study also showed that ticagrelor was associated with fewer deaths following pulmonary adverse events and sepsis compared to clopidogrel. It is unknown whether ticagrelor's additional property of inhibiting cellular adenosine uptake might underlie this observation. The aim of this study was to characterise the offset of ticagrelor's activity in inhibiting platelets and also in inhibiting cellular adenosine uptake in ACS patients. Methods: Patients admitted with ACS, treated with ticagrelor and referred for CABG were recruited. Venous blood was drawn from patients at the following 6 timepoints: 2 hours (h), 24 hour, 48 hour, 72 hour, 96 hour, and 120 hour after the last dose of ticagrelor prior to CABG. Whole-blood aggregometry was carried out using the Multiplate analyzer with adenosine diphosphate 6.45 µM as agonist and the final value of area under the curve (AUC) (units, U) was recorded. Results were analysed using linear mixed models. A local protocol was referred to, where an AUC of >50U supports safe progression to surgery, while values 50U indicates need for re-testing 24–48 hours later. Inhibition of adenosine uptake was determined by measuring the adenosine plasma concentration using liquid chromatography. Results: 13 patients were recruited, all of whom received ticagrelor prior to CABG surgery. At 96 hour post ticagrelor, the mean AUC was 82.8U, (95% confidence interval, 60.4, 105.2). Only at 96 hour was the lower limit of the confidence interval >50U. From the mixed model analysis, the comparison between 72 hour and 120 hour post ticagrelor showed a significant difference (p=0.007) while 96 hour and 120 hour showed no significant difference (p=1.000). Adenosine plasma concentration was measured in 7 patients who received ticagrelor and showed no significant difference in adenosine plasma concentration across all timepoints. Conclusion: ACS patients might be safe to undergo CABG surgery 4 days after the cessation of ticagrelor. Ticagrelor might have no measurable effect on adenosine transport in ACS patients.